An Exploration into the Pedagogical Benefits of Using Social Media: Can Educators Incorporate Social Media into Pedagogy Successfully? A work in progress - Williams, Ryan Thomas (ABC Journal of Advanced Research, 2020)
Many social networking sites have been thought to break down traditional hierarchies in terms of society and global geography (Lewis 2017). As an example, Twitter empowers learners to engage with individuals from all over the world, often sharing educational resources for free. This ‘work in progress’ paper adopts a mixed-methods model to explore if social media can be incorporated successfully with pedagogy. In total, 431 participants took part in this study. Of those, 411 completed the survey, and 20 were subjects in the interviews. Teachers described professional reasons and social reasons why they do not use social media regularly in their pedagogy. One emerging theme is that CPD appears to be underdeveloped in this area, as teachers report that TEL training focuses on administrative uses of a product rather than pedagogical benefits. This has implications on how social media could be used as a pedagogical tool and addresses gaps in the literature in this area. This direction of social media in the classroom remains unclear, however, this study aims to offer a framework for educators when using social media strategies.